Spexin level in growth hormone deficiency Iraqi children - L. A. Ghannawi; K. Gharab; M. A. Hadi; O. Y. Shakir; A. M. Rahmah (The Ukrainian Biochemical Journal)
Spexin (SPX) is a newly discovered brain adipokine implicated in various homeostatic functions including metabolism, energy balance, endocrine processes and growth hormone (GH) production in particular. At the same time, the growth-promoting effects of GH are influenced by Insulin-like growth factor-1 (IGF‑1) and vitamin D3. The aim of this study was to investigate the possible involvement of SPX in growth hormone deficiency (GHD) in children. The research involved 90 children (40 with growth hormone deficiency and 50 healthy controls aged 5-14). Serum levels of GH, IGF and vitamin D3 were tested using a chemiluminescent immunoassay, that of SPX – by Elabscience ELISA Kit. The results revealed that children with GHD had significantly higher SPX levels compared to the control group. No significant difference in IGF-1 and vitamin D3 levels between patients and control groups was observed. In the GHD group, we found a significant negative correlation between SPX and GH levels; at the same time, there was no correlation between SPX and D3 levels. These findings suggest that the changes in SPX levels may contribute to growth hormone deficiency.